Standardisasi SOP Internal Berbasis SIG untuk Rekomendasi Fasilitas Ibadah di Maluku - Moh. Abduh Daeng Matta (JURNAL ILMIAH GEMA PERENCANA, 2025)
The Maluku Province, consisting of over 1,300 islands with limited regular ferry services covering only about 40 % of remote villages, experiences a pronounced gap between the community’s ideal need for adequate, accessible, and context‑sensitive worship facilities and the actual provision on the ground. The primary issue stems from the absence of internal spatial metadata guidelines and Public Participation GIS (PPGIS) procedures within the Maluku Regional Office of the Ministry of Religious Affairs, despite existing regulatory frameworks—Joint Regulation of the Minister of Religious Affairs No. 9/2006 & Minister of Home Affairs No. 8/2006, Ministerial Regulation No. 19/2019, and Minister of Home Affairs Regulation No. 86/2017—governing permits, technical building standards, and GIS‑based e‑planning. This study employs mixed methods: quantitative descriptive statistics of secondary data (regulatory documents, e‑planning platform, PPGIS shapefiles, Planning Bureau reports) and USG (Urgency–Seriousness–Growth) scoring, alongside qualitative semi‑structured interviews with ten key informants (regional officials, GIS planners, community affairs, ICT agency, religious leaders). Spatial analysis using buffer and overlay in QGIS, thematic coding per Miles & Huberman, triangulation, and member checking ensure validity. Findings reveal only 60.7 % village coverage, heterogeneous metadata formats, and procedural and technical coordination barriers. It concludes that issuing a Regional Office Decree on an Internal SOP for GIS‑PPGIS (Alternative 1) is the most critical intervention.